Numerical simulation of dynamic characteristics of droplet in oil under a CPPM electric field. (2nd February 2022) - Gong, Haifeng; Liao, Zhixiang; Peng, Ye; Qiu, Zhi; Yu, Bao; Zhang, Youyu
Highlights: Dynamics model of droplet deformation in oil under CPPM electric field was developed. The effects of pulse width and electric field intensity has been investigated. The largest Lyapunov exponent indicates the droplet deformation is chaotic motion. The chaos of droplet deformation decreases with the increase in pulse width. Chaotic deformation disappears and droplet splits at high electric field intensity. Abstract: The size of droplets in oil are dynamically changes during demulsification, thereby changing the optimum demulsification electric field frequency. Thus, the constant pulsed electric field cannot meet the requirement of optimum frequency. The variable frequency pulsed electric field can cater to the change in optimum demulsification frequency, and has high demulsification ability. However, the dynamic characteristics of the droplet in oil at the variable frequency pulsed electric field are unclear. Therefore, a chaotic pulse position modulation (CPPM) electric field is considered a type of variable frequency pulsed electric field, where the pulse frequency is chaotic but pulse width and field intensity are constant. The droplet deformation dynamic model under the CPPM electric field is established by applying finite element method. The dynamic and chaotic characteristics of the droplet deformation in oil in this electric field are investigated, and the influence of pulse width and electric field intensity on droplet deformation is discussed. Results show that the deformation of droplet in oil is nonstationary vibration with the action of the CPPM electric field, and its deformation is chaotic vibration. The chaos of droplet deformation decreases with the increase in pulse width, and an optimum pulse width can be found to make the droplet have large deformation ratio and high vibration times. The deformation ratio of droplet can be increased by increasing the electric field intensity, but the droplet are easy to split and the deformation is no longer chaotic at high electric field intensity, and an optimum electric field intensity can be found to make the droplet have large deformation ratio and deformation stability.